Gut Microbiota Dysbiosis Associated With Altered Production of Short Chain Fatty Acids in Children With Neurodevelopmental Disorders - Bojović, Katarina; Ignjatović, Ður -d ica; Soković Bajić, Svetlana; Vojnović Milutinović, Danijela; Tomić, Mirko; Golić, Nataša; Tolinački, Maja (Frontiers in Cellular and Infection Microbiology, 2020)
While the gut microbiota dysbiosis has been linked with autism, its role in etiology of other neurodevelopmental disorders (NDD) is mainly underexplored. To our knowledge this is the first study evaluating gut microbiota diversity and composition in 36 children from Republic of Serbia diagnosed with some of the NDD and 28 healthy children. The results revealed the increased incidence of potentially harmful bacteria, closely related to Clostridium species, in the NDD patients’ group compared to the Control group: Desulfotomaculum guttoideum (P<0.01), Intestinibacter bartlettii (P<0.05) and Romboutsia ilealis (P<0.001). On the other hand, significantly lower diversity of common commensal bacteria in the group of patients was noticed. Enterococcus faecalis (P<0.05), Enterococcus gallinarum (P<0.01), Streptococcus pasteurianus (P<0.05), Lactobacillus rhamnosus (P<0.01) and Bifidobacteria sp. were detected in lower number of patients or were even absent in some NDD patients’ groups. In addition, butyrate producing bacteria Faecalibacterium prausnitzii (P<0.01), Butyricicoccus pullicaecorum (P<0.05) and Eubacterium rectale (P=0.07) were less frequent in the patients’ groups. In line with that, the levels of fecal short chain fatty acids (SCFAs) were determined. Although the significant differences in SCFAs levels were not detected between NDD patients’ and Control group, a positive correlation was noted between number of rDNA amplicons obtained with universal primers and level of propionic acid, as well as a trend for level of total SCFAs and butyric acid in the Control group. This correlation is lost in the NDD patients’ groups indicating that NDD patients’ microbiota differs from microbiota of healthy children in the presence or number of strong SCFAs-producing bacteria. According to range-weighted richness index it was observed that microbial diversity was significantly lower in the NDD patient group. Our study reveals that the intestinal microbiota from NDD patients differs from the microbiota of healthy children. It is hypothesized that early life microbiome might have impact on GI disturbances and accompanied behavioral problems frequently observed in patients from a broad spectrum of NDD.